Study Comparative of Antenna for Microwave Imaging Applications - Rachmat Agus Kurdyanto; Nurhayati Nurhayati; Puput Wanarti Rusimamto; Farid Baskoro (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2020)
AbstractMicrowave can be applied for telecommunicaions, radar and microwave imaging. This wave has been widely used in everyday life, such as in the industrial word in the fields of robotics, microwave vision, imaging burrier objects, vehicular guidance, biomedical imaging, remote sensing, wheater radar, target tracking, and other apllications. Microwave imaging is a technology that uses electromagnetic waves at frequencies from Megahertz to Gigahertz. Utilization of microwave imaging in addition to information technology and telecommunications, this wave application can be used to process an image because of its ability to penetrate dielectric materials. The purpose of writing this article is to determine microwave imaging application, the working principle of antennas used for microwave imaging applications and antenna specifications used for microwave imaging applications. Microwave imaging research has been carried out using several different type of antennas such as vivaldi and monopole antennas. Where the signal tha is transmitted and will be exposed to the object will send a different return signal so that an image of an object will be obtained which will be processed on the computer. The working frequency of the antenna for microwave imaging applications is in a wide frequency range (UWB antenna). The antennas that are applied include the vivaldi antenna which works at a frequency of 1-11 GHz and a monopole antenna that works at a frequency 1,25-2,4 GHz for biomedical imaging applications, while for radar applications in the construction field it can use a frequency of 0,5-40 GHz.